Fertilizer value and nitrogen transfer efficiencies with clover-grass ley biomass based fertilizers - Benke, Anna Pia; Rieps, Ann-Marleen; Wollmann, Iris; Petrova, Ioana; Zikeli, Sabine; Möller, Kurt (Nutrient cycling in agroecosystems, 2017)
In temperate regions, legume-based green manures are a key element of organic rotations. However, specialized farms lack sufficient mobile organic fertilizers. To gain a better understanding of the N flows and the nitrogen (N) and phosphorus (P) fertilizer value of different clover-grass-based fertilizers (biogas digestate, compost, silage and fresh clover-grass obtained from clover-grass ley biomass), we assessed their fertilizer value. Nitrogen and P offtake by the ryegrass was used to assess the short-term effects. The data were completed using model calculations to assess the field-to-field N-transfer efficiencies and the overall N-transfer efficiencies. The greatest plant N offtake was achieved with digestates (64%) and the lowest from the compost (6%) and solid farmyard manure (14%). The mineralization rate was positively related to the NH 4 + –N/total N ratio ( P < 0.01, r 2 = 0.82). The model calculations indicate that the overall short-term N-transfer efficiencies are driven by the field-to-field N-transfer efficiency and the field-to-crop transfer efficiency. However, in the long term, model calculations indicate that a high field-to-field N-transfer efficiency is the key strategic approach when aiming to achieve cropping systems with a high overall long-term N-transfer efficiency. Consequently, the results showed that aerobic decomposition (composting) significantly lowered field-to-field as well as field-to-crop N-transfer rates. The relative P use efficiency strongly differed among the fertilizers. In particular, freshly cut clover-grass and solid manure increased P availability and led to an increase of plant P offtake that was higher than the amount of P supplied.